2004
DOI: 10.1007/s10533-004-0371-z
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deposition and carbon sequestration in alpine meadows

Abstract: Abstract. Nitrogen deposition experiments were carried out in alpine meadow ecosystems in Qinghai-Xizang Plateau in China, in order to explore the contribution of nitrogen deposition to carbon sequestration in alpine meadows. Two methods were used in this respect. First, we used the allocation of 15 N tracer to soil and plant pools. Second, we used increased root biomass observed in the nitrogen-amended plots. Calculating enhanced carbon storage, we considered the net soil CO 2 emissions exposed to nitrogen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 65 publications
3
17
0
2
Order By: Relevance
“…Previous studies indicated that the respiration rate at about 9:00 am (local time) was close to the average daily respiration rate in the same alpine meadow (Xu et al 2004b;Zhang et al 2006). Therefore, R ec and R s measurements in this study were made between 9:00 and 11:00 am (local time).…”
Section: Field Sampling and Measurementsmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies indicated that the respiration rate at about 9:00 am (local time) was close to the average daily respiration rate in the same alpine meadow (Xu et al 2004b;Zhang et al 2006). Therefore, R ec and R s measurements in this study were made between 9:00 and 11:00 am (local time).…”
Section: Field Sampling and Measurementsmentioning
confidence: 58%
“…In contrast, soil CO 2 emissions increase substantially in response to N fertilization. For example, chronic atmospheric N deposition stimulated soil CO 2 efflux in an alpine meadow by increasing available N and promoting plant growth (Xu et al 2004b;Fang et al 2012). In addition, enhanced decomposition rates caused by an increased production of plant litter under nutrient enrichment also resulted in higher CO 2 emissions and dissolved organic C release from peat bogs (Bragazza et al 2006).…”
Section: Responses Of Ecosystem and Soil Respiration To Nutrient Fertmentioning
confidence: 99%
“…Besides aboveground parts, roots also contribute to N input. Chen and Wang (2000) and Xu et al (2004) approximated that one third of the roots in alpine meadows were replaced in 1 year and observed a 50% root turnover in temperate steppes. Assuming a similar root to shoot ratio for legumes as the whole plant community, the N 2 -fixation in the legume roots amounts to 0.72 and 0.32 g N m -2 in the alpine meadow and the temperate steppe, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated N deposition can affect soil CO 2 emission through changes in litter decomposition, root respiration and soil microbial respiration rates [32]. N deposition can alleviate N-limitation and accelerate microbial activities.…”
Section: Effect Of N Deposition On Soil Co 2 Emissionmentioning
confidence: 99%